2010
DOI: 10.1111/j.1530-9290.2010.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle of Titanium Dioxide Nanoparticle Production

Abstract: Life cycle impact of emissions, energy requirements, and exergetic losses are calculated for a novel process for producing titanium dioxide nanoparticles from an ilmenite feedstock. The Altairnano hydrochloride process analyzed is tailored for the production of nanoscale particles, unlike established commercial processes. The life cycle energy requirements for the production of these particles is compared with that of traditional building materials on a per unit mass basis. The environmental impact assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 14 publications
1
53
0
4
Order By: Relevance
“…Another gap apparent in the nano-LCA literature is that of lack of information on the production processes (Osterwalder et al 2006;Bauer et al 2008;Khanna et al 2008;Kushnir and Sandén 2008;Khanna and Bakshi 2009;Grubb and Bakshi 2011). Khanna et al (2008) caution that the industrial scale nano-LCA results could be gross overestimates as the nano-manufacturing processes are likely to become more efficient with higher yields over time and volume.…”
Section: Lca Studies On Nanomaterials-a Reviewmentioning
confidence: 93%
“…Another gap apparent in the nano-LCA literature is that of lack of information on the production processes (Osterwalder et al 2006;Bauer et al 2008;Khanna et al 2008;Kushnir and Sandén 2008;Khanna and Bakshi 2009;Grubb and Bakshi 2011). Khanna et al (2008) caution that the industrial scale nano-LCA results could be gross overestimates as the nano-manufacturing processes are likely to become more efficient with higher yields over time and volume.…”
Section: Lca Studies On Nanomaterials-a Reviewmentioning
confidence: 93%
“…It is clearly evident that the limestone-cement mixes have a lower environmental impact compared to plain cement paste mix, whereas TiO 2 -cement mixes have considerably higher environmental impacts (''costs''). The reason for high environmental impact by the TiO 2 -cement mix is because of the significantly higher energy and emissions ''costs'' of TiO 2 manufacturing process compared to cement production [42,44]. By comparing the environmental ''costs'' of the ordinary Portland cement mix and limestone-cement mixture, it can be observed that the addition of 5% limestone results in almost a 5% decrease in the various impact categories, as might be expected.…”
Section: Life Cycle Analysismentioning
confidence: 59%
“…In recent years, research related to photocatalytic concrete and its NO x degradation rate, durability performance, reaction kinetic models and environmental impact through life-cycle assessment has gained considerable attention (Poon and Cheung 2007, Diamanti et al 2008, Hunger et al 2008, Dylla et al 2011, Grubb and Bakshi 2011. Literature reveals that although, SO x , PM 10 , VOCs, ground level ozone and NO x , are the most critical air pollutants, experimental and analytical models have predominantly focused on NO x .…”
Section: Background -Photocatalysis Of Concrete Materialsmentioning
confidence: 97%